2018
DOI: 10.12688/f1000research.13167.1
|View full text |Cite
|
Sign up to set email alerts
|

JAK inhibitors for the treatment of myeloproliferative neoplasms and other disorders

Abstract: JAK inhibitors have been developed following the discovery of the JAK2V617F in 2005 as the driver mutation of the majority of non- BCR-ABL1 myeloproliferative neoplasms (MPNs). Subsequently, the search for JAK2 inhibitors continued with the discovery that the other driver mutations ( CALR and MPL) also exhibited persistent JAK2 activation. Several type I ATP-competitive JAK inhibitors with different specificities were assessed in clinical trials and exhibited minimal hematologic toxicity. Interestingly, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 180 publications
3
109
0
Order By: Relevance
“…In the present study, we also showed that treating ESCC cells with HXR9 caused apoptosis and inhibited cell proliferation and tumor growth in all of the lines tested. It has been reported that a rapid increase in c‐fos expression as a response to HOX/PBX inhibition was activated to induce apoptosis, which was also confirmed in our study. In addition, we found that PI3K‐AKT and JAK‐STAT pathway repression may be a response to antiproliferation and proapoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we also showed that treating ESCC cells with HXR9 caused apoptosis and inhibited cell proliferation and tumor growth in all of the lines tested. It has been reported that a rapid increase in c‐fos expression as a response to HOX/PBX inhibition was activated to induce apoptosis, which was also confirmed in our study. In addition, we found that PI3K‐AKT and JAK‐STAT pathway repression may be a response to antiproliferation and proapoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Ruxolitinib (a JAK1/2 inhibitor) reduces splenomegaly and constitutional symptoms in MF. However, over 50% of patients fail to achieve a response or lose it over time (Tefferi & Pardanani, ; Vainchenker et al , ).…”
mentioning
confidence: 99%
“…Now, several other candidate agents that target pathways activated by the dysfunctional JAK2 signaling, such as STAT, PI3K/AKT, and MEK/ERK, and the associated NF-κB inflammatory pathways, have rapidly been emerging. 85 Each of these could prove valuable, even after resistance to ruxolitinib as a single agent has developed. For example, inhibitors of BET proteins, implicated in NF-κB pathways, have been shown to synergize with ruxolitinib in vitro and in vivo, and one (CPI-0610) is now being tested in a clinical trial both with and after ruxolitinib.…”
Section: Sm In the Midostaurin Eramentioning
confidence: 99%
“…Ruxolitinib, and other type I JAK2 inhibitors, were rationally designed to inhibit the constitutive JAK2 signaling that is generally believed to lead to the development of MPN. Now, several other candidate agents that target pathways activated by the dysfunctional JAK2 signaling, such as STAT, PI3K/AKT, and MEK/ERK, and the associated NF‐κB inflammatory pathways, have rapidly been emerging . Each of these could prove valuable, even after resistance to ruxolitinib as a single agent has developed.…”
Section: Introductionmentioning
confidence: 99%